An overview on rape punishments in Malaysia / Siti Nabila Hamzah, Rainah Igong and Norhayati Jusoh - Hamzah, Siti Nabila; Igong, Rainah; Jusoh, Norhayati (2007)
This project attempts to identify the sufficiency of Section 376 of Penal Code on the punishment of rape in Malaysia. Data were gathered from questionnaires, interviews and from the observation on the Malaysian law on rape. The report concludes that there are various types of punishments to a rape offender in Malaysia which might be discussed and introduced for future benefits.